Respuesta :
Answer:
[tex]f(1)=-6[/tex]
[tex]f(n)=f(n-1)(-3)[/tex]
Step-by-step explanation:
We are given that
[tex]f(n)=2\cdot (-3)^n[/tex]
We have to complete the recursive formula of f(n).
Substitute n=1
[tex]f(1)=2\cdot (-3)[/tex]
[tex]f(1)=-6[/tex]
[tex]f(2)=2\cdot (-3)^2=18[/tex]
[tex]f(3)=2\cdot (-3)^3=-54[/tex]
[tex]\frac{f(2)}{f(1)}=\frac{18}{-6}=-3[/tex]
[tex]\frac{f(3)}{f(2)}=\frac{-54}{18}=-3[/tex]
It forms geometric sequence because the ratio of two consecutive terms are equal.
Therefore, the recursive formula
[tex]f(n)=f(n-1)r[/tex]
[tex]f(n)=f(n-1)(-3)[/tex]